Surgical aortic valve replacement – challenges in short and long-term management - Björn, Rikhard (fi=Turun yliopisto|en=University of Turku|, 2026)
The only curative treatments for aortic valve defects are valve repair or valve replacement using either a mechanical or a biological prosthesis. An aortic valve replacement can be performed via transcatheter aortic valve implantation (TAVI) or open-heart surgery. Outcomes following a surgical aortic valve replacement (SAVR) are generally favorable; however, the procedure carries inherent risks. Atrial fibrillation (AF) is the most common complication following SAVR, occurring in approximately 32.9% to 74.0% of patients during the index hospitalization and in 18.5% to 44.5% later postoperatively. Among patients undergoing a mechanical aortic valve replacement, stroke remains one of the most feared complications, with an estimated annual incidence ranging from 0.4% to 1.8%. Due to the thrombogenic nature of mechanical valves, lifelong anticoagulation therapy is required. However, this therapy increases the risk of major bleeding events. This thesis investigated the complications following a bioprosthetic and a mechanical SAVR, with a focus on new-onset atrial fibrillation (NOAF), major stroke, and bleeding events, as well as their associations with antithrombotic therapy. The findings indicate that NOAF occurs in a substantial proportion of patients after both a bioprosthetic and a mechanical SAVR. Furthermore, patients who develop NOAF during their initial hospitalization are at high risk of recurrent AF later in life and all-cause mortality in both bioprosthetic and mechanical SAVR cohorts. In addition, the incidence of early postoperative major bleeding is significantly higher than that of a major stroke following a bioprosthetic and a mechanical SAVR. The risk of major bleeding remains higher during both early and late periods in patients with a mechanical aortic valve prosthesis, while in patients with bioprosthesis, the risks of stroke and bleeding are nearly equal. In the future, the guidelines should account for bleeding risk in addition to thrombotic complications in patients undergoing SAVR.

Aortan kirurginen tekoläppäleikkaus – haasteet lyhyt- ja pitkäaikaishoidossa Aorttaläpän vikojen ainoat parantavat hoitomuodot ovat läpän korjaus tai vaihto mekaaniseen tai biologiseen tekoläppään. Aorttaläppä voidaan vaihtaa joko katetriläppätoimenpiteellä (TAVI) tai avosydänleikkauksella. Kirurgisen aorttaläpän vaihdon tulokset ovat lähtökohtaisesti hyviä, mutta toimenpiteeseen liittyy merkittäviä riskejä. Yleisin komplikaatio avosydänleikkauksen jälkeen on eteisvärinä, jota esiintyy aiempien tutkimusten mukaan 32.9–74.0 %:lla potilaista sairaalahoidon aikana ja 18.5–44.5 %:lla myöhemmässä seurannassa. Näiden esiintymisen keskinäisestä suhteesta ja erityisesti pitkäaikaisseurannasta on kuitenkin rajallisesti tietoa. Mekaanisen aortan tekoläppäleikkauksen läpikäyneillä potilailla pelätyin komplikaatio on kuitenkin aivoinfarkti, jonka ilmaantuvuus on 0,4–1,8% vuodessa. Mekaanisten läppien trombogeenisyyden vuoksi potilaat tarvitsevat elinikäisen verenohennuslääkityksen, mikä puolestaan lisää vakavien verenvuotojen riskiä. Tässä väitöskirjassa tutkittiin kirurgisen aortan tekoläppäleikkauksen komplikaatioita sekä sairaalahoitojakson aikana että pitkäaikaisseurannassa. Erityisesti tarkasteltiin uuden eteisvärinän, vakavien aivoinfarktien ja verenvuotojen esiintyvyyttä sekä niiden yhteyttä verenohennuslääkkeiden ja muiden veren hyytymistä estävien lääkkeiden käyttöön. Tutkimuksen tulokset osoittavat, että uusi eteisvärinä on yleinen komplikaatio sekä biologisen että mekaanisen aortan tekoläppäleikkauksen jälkeen. Uuden eteisvärinän esiintyminen sairaalahoidon aikana ennustaa myöhempää eteisvärinän uusiutumista ja on yhteydessä kokonaiskuolleisuuteen molemmissa potilasryhmissä. Molemmissa potilasryhmissä varhaisen leikkauksenjälkeisen vakavan verenvuodon ilmaantuvuus on merkittävästi korkeampi kuin vakavan aivohalvauksen. Pitkällä aikavälillä vakavan verenvuodon riski säilyy suurempana mekaanisen aorttaläppäproteesin saaneilla potilailla, kun taas bioproteesipotilailla aivohalvauksen ja verenvuodon riskit ovat lähes samansuuruiset. Kansainvälisten hoitosuositusten tulisi jatkossa tarkemmin huomioida verenvuotoriski aortan tekoläppäleikkauksen läpikäyneillä potilailla.